2017
DOI: 10.1371/journal.pone.0182039
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer cell/fibroblast co-culture induces M2 like macrophages that influence therapeutic response in a 3D model

Abstract: Pancreatic cancer (PC) remains one of the most challenging solid tumors to treat with a high unmet medical need as patients poorly respond to standard-of-care-therapies. Prominent desmoplastic reaction involving cancer-associated fibroblasts (CAFs) and the immune cells in the tumor microenvironment (TME) and their cross-talk play a significant role in tumor immune escape and progression. To identify the key cellular mechanisms induce an immunosuppressive tumor microenvironment, we established 3D co-culture mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(137 citation statements)
references
References 47 publications
5
132
0
Order By: Relevance
“…In addition, bioprinting techniques have led to the biofabrication of accurate models that can recreate the biophysical and biochemical characteristics of a given tissue ( 292 ). Thus, in the near future, the cross-talk among the different components of the TME will be analyzed using more and more precise 3D models and organoids from a given patient to test the sensitivity to selected targeted therapy ( 289 , 294 , 302 , 306 , 311 313 ).…”
Section: Research Gaps and Future Developmentsmentioning
confidence: 99%
“…In addition, bioprinting techniques have led to the biofabrication of accurate models that can recreate the biophysical and biochemical characteristics of a given tissue ( 292 ). Thus, in the near future, the cross-talk among the different components of the TME will be analyzed using more and more precise 3D models and organoids from a given patient to test the sensitivity to selected targeted therapy ( 289 , 294 , 302 , 306 , 311 313 ).…”
Section: Research Gaps and Future Developmentsmentioning
confidence: 99%
“…Co-cultures serve as an alternative. MCTS of nonsmall-cell lung cancer, pancreatic, and breast cancer tumor cells supplemented with fibroblasts and/or macrophages have been described (114)(115)(116). The tumor-associated macrophages (TAM) obtained in these models present similar characteristics to those observed in tumors, namely increased resistance to treatment and an improved cytokine environment.…”
Section: Spheroid Modelsmentioning
confidence: 97%
“…FAP + CAFs are the main tumoral source of CXCL12, which was involved in disadvantageous T cell formation in the TME of a mouse model of PDAC 83 . 3D coculture of monocytes with PCCs and fibroblasts was shown to increase the production of immunosuppressive cytokines, such as IL-6, IL-8, IL-10, GM-CSF and M-CSF, which are known to promote the polarization of M2-like macrophages and MDSCs 84 . Another study found that activated CAFs could induce peripheral blood mononuclear cells to differentiate into MDSCs via a STAT3-dependent mechanism 43 .…”
Section: Cafs Regulate Tumor Immunity In Pdacmentioning
confidence: 99%